Debunking the myth: low knowledge levels of HBV infection among Asian American college students - Min-Jin Kim; Haeok Lee; Peter Kiang; Paul Watanabe; Maria I Torres; Patricia Halon; Ling Shi; Daniel R Church (Elsevier, 2015)
Objective: To examine the hepatitis B virus (HBV)-related knowledge among Asian American college students and to determine whether there are significant differences in the level of HBV knowledge among Asian American subgroups. Methods: A cross-sectional survey was self-administered to assess a sample of 258 Asian American students' knowledge about HBV at the campus of the research site. Results: Knowledge regarding transmission and consequences of HBV infection was poor. Of a possible knowledge score of 14, the median number of correct answers was eight. There were no significant differences between the subgroups of Asian American college students in total knowledge of HBV infection. Conclusion: The findings of this study point to the fact that the lack of knowledge and awareness is not limited to community settings only but also includes higher education environment. This finding brings to the forefront the importance of HBV education for Asian American college students.